A scheme for spin-selective electron localization in Mn3Ga Heusler material - Wollmann, Lukas; Fecher, Gerhard H.; Chadov, Stanislav; Felser, Claudia (Journal of Physics D: Applied Physics, 2015)
We demonstrate that tetragonal Mn3Ga Heusler material allows for a new possibility of adjusting an electric current by means of the so-called spin-selective localization of conduction electrons. On the basis of a first-principles analysis, we propose possible chemical substitutes for Mn, which, when used in small quantities, can lead to a disorder-induced localization of the conduction electrons in a single spin channel. Replacement of the Mn in Mn3-xYxGa with other 3d transition metals Y is known not to change the tetragonal structure for a certain range of x. For Y = Co the range is x ≤ 0.5. Therefore, substitution of Co for Mn is used in the present work as a prototype procedure for a detailed demonstration of the underlying physical mechanisms.
CRIS-Team Scopus Importer:2023-03-20
Keywords: coherent potential approximation; disorder engineering; Heusler alloys; localisation; spin polarisation